Mesenchymal Stem Cells and Cardiovascular Diseases - Ayapati Gautam Mehdi; Vikram Aiman Ayapati; Avinash B; A. A. Khan; Nirmal Kumar Lohiya; Vijay Lakshmi; Dharma Rakshak Ayapati; Roya Rozati (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Stem cell therapy has begun as a promising and novel approach for the treatment of various diseases. Stem cell therapy involves the identification of correct cells, area of transplantation. Transplantation of functional and healthy stem cells help to renewal of damaged cells and repair injured tissue. Stem cell isolated from bone marrow were the first cell type used in preclinical and clinical investigations for the have been extended to the use of various populations of stem cells. But there are very few studies which show the roles of stem cells in cardiovascular disease. Cardiovascular Disease (CVD) constitutes the most important cause of mortality and morbidity worldwide. CVD represents a group of disorders connected with the defeat of cardiac function. In spite of significant advances in the understanding of the pathophysiological mechanisms of the disease, the problem of cardiac tissue loss has not yet been addressed. Only few therapeutic approaches suggest through tissue repair and regeneration. The most of treatment options aim to control the scar formation and adverse remodeling, while improving myocardial function. Of all the existing therapeutic approaches, the problem of cardiac tissue loss is addressed uniquely by heart transplantation. This review addresses the present state of research as regards stem cell therapy for CVD.